The Effectiveness of Brisk Walking Exercise on Blood Pressure Changes in Older Adults with Hypertension - Laili Ulfiyani; Abi Muhlisin (Jurnal Keperawatan Profesional, 2026)
Hypertension is a common chronic disease in the elderly population and can increase the risk of cardiovascular disorders if not optimally managed and controlled. In addition to pharmacological therapy, non-pharmacological interventions in the form of physical activity are recommended as part of hypertension management. Brisk walking exercise, also known as brisk walking, is a form of physical activity that is practical and easy for the elderly to perform. The purpose of this case study was to examine changes in blood pressure in elderly women with hypertension after brisk walking exercise. This study used a descriptive research method with a case study approach through the application of the nursing process. The study subjects consisted of four elderly women with hypertension. The nursing process was carried out through the stages of assessment, establishing a nursing diagnosis, planning, implementation, and evaluation. The brisk walking exercise intervention was administered five times over a two-week period, with each session lasting approximately 30 minutes. Blood pressure checks were performed pre-intervention and post-intervention. All participants showed a decrease in both systolic and diastolic blood pressure after the brisk walking exercise program. The results showed that brisk walking exercise is effective in reducing blood pressure in elderly women with hypertension. The implication of this study is that brisk walking exercise can be recommended as a safe, easy-to-implement, and low-cost community nursing intervention in efforts to control blood pressure and prevent complications of hypertension in the elderly.